The Governance of Information Technology and Deliberative Democracy: Study of The Law on Information and Electronic Transactions (ITE) - Devi Tri Indriasari; Ade Armando (Green Publisher Indonesia, 2023)
This study begins from the problems that arise related to the discussion of the ITE Bill in the DPR, as well as the revision and implementation of the ITE Law. Especially issues related to cases that cause polemics and disturb the feeling of justice. This study aims to describe the construction of social reality in the form of thoughts, ideas, and discourses behind the implementation of the ITE Law. This study is also intended to determine the involvement of public participation in influencing the processes of legal formation and public policy in state institutions as described by Habermas (1989). So far, the growing assumption is that the ITE Law has limited freedom of expression and there is a state motivation to demand civil society compliance through repressive state apparatus. The question to be answered in this research is to what extent are the principles of deliberative democracy found in the social processes that occur in the discussion of the ITE Bill, revision and implementation of the ITE Law? Our argument is that the process of discussing the revision of the ITE Law and evaluating this law is not based on the principles of deliberative democracy, thereby strengthening the regime of digital authoritarianism.